Using a personalized DVD to prescribe an exercise program to older people post-hip fracture enhances adherence to the exercises: A feasibility study - Moran, L.; Francis-Coad, J.; Patman, S.; Hill, Anne-Marie (2015)
Optimum recovery from hip fracture has been linked to the provision of effective rehabilitation, but levels of adherence vary among older patients. In this feasibility study a novel personalized DVD was designed for four participants, which delivered a 5 week tailored home exercise program (HEP), with the participant being videoed completing their exercises. Treatment fidelity of the DVD HEP was evaluated, including participants' perceptions of and response to the DVD-HEP, which was explored using diaries and interviews and analyzed thematically. Secondary outcome measures including exercise adherence and self-efficacy for exercise were analyzed using descriptive statistics. Levels of adherence to the HEP were 1.2-3.5 times more than the minimum prescribed dose and participants demonstrated higher levels of self-efficacy for exercise. Adherence was found to be enhanced by physical improvement, positive self-reflection about engagement in the DVD-HEP, the format of the DVD, and increased self-efficacy. Personalized DVDs may be a feasible method of promoting adherence to home exercise programs among older patients.